Investigation of LaBr3(Ce) detectors at the RITU focal plane - Nefodov, Oleksandr (2015)
The aims of this master thesis were to determine the absolute detection efficiency of the LaBr3(Ce) detectors installed at the RITU focal plane, to study the effect of planar Ge-detector on the LaBr3(Ce) efficiency and to investigate the possibility of half-life measurements with the detectors in a coincidence setup having distributed recoil ions produced by the RITU separator. Time spectra were collected by moving a point radioactive source from one edge of the implantation detector to the other to imitate the ion distribution from the RITU separator. Simulations have been exploited to explore the time spectra obtained from various ion distribution shapes and for different half-lives. A point source of 152Eu has been utilized to measure the half-life of the first 2+ state of 152Sm. The half-life obtained experimentally was equal to 1.39 ns± 0.08 ns, which agrees with the tabulated value.